General strategy of h-p adaptive solutions in structural Trefftz-type element analysis - Szybiński, Bogdan; Wróblewski, Adam; Zieliński, Andrzej P. (Computer Assisted Methods in Engineering and Science, 2001)
The paper deals with a strategy of reliable application of the Trefftz elements in the linear analysis of complex engineering structures with stress concentrators. The standard p-adaptivity is suggested in the low gradient areas. For selected large-gradient local zones certain specific T-element substructures are proposed. The h-p adaptive procedures for optimization of parameters of the substructures are numerically investigated.